Development of Augmented Reality "Sikola" Media Based on the "Megoak - Goakkan" Tradition on Cultural Diversity Material to Stimulate Reading Interest in Grade III Elementary Schools - Ni Luh Widya Ayodya Putri; Putu Aditya Antara; I Kadek Edi Yudiana (International Journal of Elementary Education, 2026)
Low reading interest among elementary school students remains a challenge in literacy and culture-based learning due to the limited use of innovative and contextual learning media, resulting in low student engagement in the learning process. This study aims to analyze, design, and evaluate the development of “Sikola,” an augmented reality-based learning medium integrated with the local tradition of Megoak-Goakkan within the topic of cultural diversity to stimulate students’ reading interest. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects involved 101 third-grade students, along with content experts, media experts, and teachers as practitioners. Data were collected through observation, interviews, questionnaires, and documentation. The instruments included validation sheets, student response questionnaires, and a reading interest scale. Data were analyzed using descriptive quantitative and qualitative techniques. The results indicate that the developed “Sikola” augmented reality media is conceptually feasible, practical, and effective in stimulating students’ reading interest through interactive visuals, culturally contextualized content, and immersive learning experiences. This media supports meaningful, engaging, and student-centered learning. The findings suggest that integrating augmented reality technology with local cultural wisdom can serve as an innovative pedagogical strategy to enhance literacy engagement and cultural awareness among elementary school students.